Non Performing Financing, Capital Adequacy Ratio, Pendapatan Bagi Hasil Dan Inflasi Terhadap Pembiayaan Bagi Hasil Pada Bank Umum Syariah - Riry Heryati (Universitas Muhammadiyah Prof. DR. HAMKA, 2018)
This study aims to find out how the influence non-performing financing (NPF), capital adequacy ratio (CAR), revenue sharing and inflation on profit sharing financing at Indonesia Islamic Banks. The population in this study is Indonesia Islamic Banks in 2013-2017 and 8 selected banks were selected. The analytical method used to test the hypothesis is analysis of multiple linear regression. The results of this study are partially non-performing financing has a negative and significant effect on the profit sharing financing, capital adequacy ratio and inflation have no effect and are not significant for profit sharing financing, revenue sharing income has a positive and significant effect on profit sharing financing. The simultaneous (F test) shows that non-performing financing, capital adequacy ratio, revenue sharing, and inflation simultaneously influence the profit sharing financing.